2021
DOI: 10.3390/polym13234186
|View full text |Cite
|
Sign up to set email alerts
|

Inner Surface Hydrophilic Modification of PVDF Membrane with Tea Polyphenols/Silica Composite Coating

Abstract: The use of Polyvinylidene fluoride (PVDF) membranes is constrained in wastewater treatment because of their hydrophobic nature. Therefore, a large number of researchers have been working on the hydrophilic modification of their surfaces. In this work, a superhydrophilic tea polyphenols/silica composite coating was developed by a one-step process. The composite coating can achieve not only superhydrophilic modification of the surface, but also the inner surface of the porous PVDF membrane, which endows the modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Chen et al 13 used polyethylene glycol dimethacrylate (PEGDMA) to graft-modify PVDF and found that the PVDF- g -PEGDMA membrane exhibited a decrease of about 80% in bovine serum albumin (BSA) adsorption compared with the original PVDF membrane, and the water contact angle decreased to 0°, greatly improving the hydrophilicity of the membrane. Xu et al 14 prepared a super-hydrophilic tea polyphenol/silica composite coating, which not only achieved super-hydrophilic modification on the porous PVDF membrane surface but also its inner surface, generating a modified membrane with excellent water permeability and ultrahigh water flux.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al 13 used polyethylene glycol dimethacrylate (PEGDMA) to graft-modify PVDF and found that the PVDF- g -PEGDMA membrane exhibited a decrease of about 80% in bovine serum albumin (BSA) adsorption compared with the original PVDF membrane, and the water contact angle decreased to 0°, greatly improving the hydrophilicity of the membrane. Xu et al 14 prepared a super-hydrophilic tea polyphenol/silica composite coating, which not only achieved super-hydrophilic modification on the porous PVDF membrane surface but also its inner surface, generating a modified membrane with excellent water permeability and ultrahigh water flux.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 33 prepared tea polyphenols-modified polypropylene membranes for oil–water separation. Xu et al 34 developed a tea polyphenols and silica composite coating to obtain a superhydrophilic PVDF membrane. Wu et al 35 investigated a simple membrane modified with tea polyphenols and titanium ions to reduce membrane contamination.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, extensive focus has been devoted to the landmark study of mussel-inspired hydrophilic modification materials [ 20 , 36 , 37 ]. Plant polyphenol-based coatings have garnered extensive research interest because of their stable surface binding affinity and drastic hydrophilicity on diverse substrates [ 38 ]. For example, Qiu et al reported a straightforward co-deposition strategy based on a reaction between catechol and polyethyleneimine to form a constructed hierarchical superhydrophilicity layer on the surface of polypropylene microfiltration membranes.…”
Section: Introductionmentioning
confidence: 99%